Angiomyxoma of the ureter imitating an upper tract urothelial carcinoma: A case report. (2018) - Zugail, Ahmed S.; Baowaidan, Faris; Comperat, Eva-Maria; Guillonneau, Bertrand; Colau, Alexandre
Highlights: Angiomyxomas are rare benign neoplasms tumors arising from the soft tissues of the perineum and pelvis. Although benign, they are notorious for their locally infiltrative nature and their propensity to recur. To the best of our knowledge, we report the first case of ureteral angiomyxoma in the literature presenting with hematuria. If an angiomyxoma were to be considered in our differential diagnosis, a ureteral biopsy could have led to an organ-sparing surgery. Abstract: Introduction: Angiomyxomas are rare benign neoplasms of mesenchymal origin arising from the soft tissues of the perineum and pelvis. Case presentation: To our knowledge, we report the first case of ureteral angiomyxoma arising de novo in a fifty-four-year-old female patient who presented with macroscopic hematuria. Discussion: The pathological findings, radiological features and operative management will be discussed. Conclusion: Angiomyxomas are notorious for their locally infiltrative nature and their propensity to recur. Clinical suspicion is capital to reach the diagnosis and a holistic care is key to a good outcome.